PENEGAKAN HUKUM TERHADAP PERIZINAN REKLAME DI KOTA SURABAYA SESUAI PERWALI NO. 21 TAHUN 2018 - Ovi Shinta Mayasari; Rusdianto Sesung (Fakultas Hukum Universitas Narotama, 2023)
Advertisements are promotional media in the field of services that aim to influence or attract the public in order to buy or pay attention to a particular product. There are many cases of violations against unlicensed billboards so that problems regarding advertisement tax in each region always seem to occur and raise many questions about the function of oversight of billboards that has been carried out so far. One of the efforts to control billboards is through the imposition of administrative sanctions. Administrative sanctions are the core of administrative law enforcement used by authorities as a reaction to non-compliance with state administrative law norms. This study aims to provide a description and academic recommendations related to the law enforcement of advertising licensing in the city of Surabaya. This study tries to discuss the form of holding billboards and imposing sanctions on violations of billboard licensing laws in the city of Surabaya. The conclusion of this study is that the form of holding billboards is a violation of technical provisions, billboards are not licensed, SIPR expires, billboards are blank material and taxes are in arrears as stated in Perwali No. 21 of 2018 which is the basis for the implementation of billboards in the city of Surabaya, while the imposition of sanctions for violations of advertising licensing laws by imposing administrative sanctions in the form of written warnings, freezing of SIPR, sealing of billboard buildings, revocation of SIPR, placing a cross on billboard material and/or publishing in the mass media; and/or demolition of advertisements. It is hoped that billboard organizers will comply more with the established rules so as to create legal awareness and reduce the risks arising from violations. The active role of various parties, both regional apparatus and the community, is also needed to control oversight of advertisement violations.Keywords: advertising violations, supervision, administrative sanctions